2006
DOI: 10.1521/aeap.2006.18.5.390
|View full text |Cite
|
Sign up to set email alerts
|

Woman to Woman: Coming Together for Positive Change—Using Empowerment and Popular Education to Prevent HIV in Women

Abstract: HIV risk is the product of social, cultural, economic, and interpersonal forces that create sex-role definitions and expectations that can lead to gender inequalities in health. Woman to Woman: Coming Together for Positive Change is an HIV/AIDS prevention intervention that takes into account that choices and actions may be constrained by poverty, gender roles, and cultural norms. This project educates and empowers, promotes women's perspectives, reaches women "where they are," and encourages women to speak of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0
8

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 17 publications
3
43
0
8
Order By: Relevance
“…3 However there is limited literature on how best to promote secondary prevention among young HIV-positive women. [3][4][5][6][7][8][9] While there have been no published secondary prevention interventions solely targeting young HIV-positive women to date, there are known social, relational, and personal factors that have the ability to act as a facilitators or barriers to HIV prevention efforts. Common social and psychological challenges such as poverty, limited access to care, gender roles, cultural norms, and limited perceived control over sexual relationships not only impact the daily lives of young, HIVpositive women in the United States but they also are known to decrease their involvement in secondary prevention efforts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 However there is limited literature on how best to promote secondary prevention among young HIV-positive women. [3][4][5][6][7][8][9] While there have been no published secondary prevention interventions solely targeting young HIV-positive women to date, there are known social, relational, and personal factors that have the ability to act as a facilitators or barriers to HIV prevention efforts. Common social and psychological challenges such as poverty, limited access to care, gender roles, cultural norms, and limited perceived control over sexual relationships not only impact the daily lives of young, HIVpositive women in the United States but they also are known to decrease their involvement in secondary prevention efforts.…”
Section: Introductionmentioning
confidence: 99%
“…Common social and psychological challenges such as poverty, limited access to care, gender roles, cultural norms, and limited perceived control over sexual relationships not only impact the daily lives of young, HIVpositive women in the United States but they also are known to decrease their involvement in secondary prevention efforts. [3][4][5][6][7][8][9] For example if violence, victimization, and poor mental health, which have been found to be pervasive among young HIV-positive youth, 10,11 are left untreated or unacknowledged, then risk factors, such as substance abuse, unsafe sexual activity, and nonadherence can increase. Likewise, relationships both sexual and nonsexual, influence the health and well-being of young HIV-positive women.…”
Section: Introductionmentioning
confidence: 99%
“…These constraints are of particular concern among more socioeconomically vulnerable women, since the literature has suggested that such women are particularly vulnerable to gender imbalance and injustices (Romero et al, 2006).…”
Section: Problem Statementmentioning
confidence: 99%
“…This approach is based on the premise that participation by community members will encourage them to "own" local problems so that they can foster local solutions [78]. For HIV prevention, empowerment may take the form of economic opportunities to reduce women's dependence, preventive measures that remain under women's control, and political and social progress to give women a voice [82].…”
Section: The Advantage Of Pa To Prevent Hiv: Empowermentmentioning
confidence: 99%